Navigating the ethics of Internet-guided self-help interventions - Borgueta, A. Maya (Clin Psychol (New York), 2018)
Internet-guided self-help (IGSH) programs have proliferated recently to treat common mental health problems such as anxiety and depression. However, technology has outpaced the development of ethical guidelines for this mode of delivery. We examine ethical challenges in this new space, including defining the role “guides” play in treatment, crisis management, and user selection and screening. IGSH programs can provide safe and ethical care when they (a) coordinate care effectively with other systems; (b) provide competent and well-defined guidance; and (c) reach users that are appropriate for and well-educated about the services they are going to receive. We argue that jurisdictional practice constraints and outdated regulatory and ethical guidelines may impede the ability of IGSH programs to maintain or even improve performance when faced with greater demand, larger populations, heterogeneous settings, and the desire for large-scale dissemination.